2017
DOI: 10.1016/j.brainresbull.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are responsible for the accumulation of β-amyloid in blood clots inside and around blood vessels in mouse brain after thrombosis

Abstract: Introduction Platelets contain beta-amyloid precursor protein (APP) as well as Aβ peptide (Aβ) that can be released upon activation. During thrombosis, platelets are concentrated in clots and activated. Methods We used in vivo fluorescent analysis and electron microscopy in mice to determine to what degree platelets are concentrated in clots. We used immunostaining to visualize Aβ after photothrombosis in mouse brains. Results Both in vivo results and electron microscopy revealed that platelets were 300–50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 70 publications
(85 reference statements)
4
67
0
Order By: Relevance
“…It is future science group www.futuremedicine.com known that during thrombosis, platelets are concentrated in clots and activated, and that activated platelets release Aβ. Enhanced release of Aβ during thrombosis suggests an additional source of Aβ in the brains of AD patients with frequent micro-thrombosis events occurring in their brains [45]. This possibility is consistent with findings in mice models and with highly conserved pattern of Aβ peptides that are known to be released by platelets in the CSF [43,45].…”
Section: Platelet Levels Of Lipids and Serotoninsupporting
confidence: 81%
See 2 more Smart Citations
“…It is future science group www.futuremedicine.com known that during thrombosis, platelets are concentrated in clots and activated, and that activated platelets release Aβ. Enhanced release of Aβ during thrombosis suggests an additional source of Aβ in the brains of AD patients with frequent micro-thrombosis events occurring in their brains [45]. This possibility is consistent with findings in mice models and with highly conserved pattern of Aβ peptides that are known to be released by platelets in the CSF [43,45].…”
Section: Platelet Levels Of Lipids and Serotoninsupporting
confidence: 81%
“…Aβ was shown to activate platelets and trigger platelet aggregation by stimulating intracellular signaling pathways that are involved in phospholipase C phosphorylation, protein kinase C (PKC) activation and increased intracellular [Ca 2+ ], resulting in increased Aβ secretion. These findings raise the possibility that Aβ activation may initiate a mutual cycle of platelet activation and Aβ release, which may play a role in Aβ upregulation in the periphery and in the CSF, further leading to the development of cerebral amyloid angiopathy [43][44][45].In summary, platelets have been studied as both a cellular model to investigate Aβ-induced responses, and a peripheral cell type that actively contribute to AD pathogenesis. Main molecules and platelet functions that can be applied as potential AD biomarkers are shown in Figure 1B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to consider that plasma amyloid peptides are not only of central nervous system (CNS) origin but have also been found to be produced by platelets, vascular walls, and skeletal muscles (Askanas, Engel, & Nogalska, 2015;Kuo et al, 2000;Li et al, 1998;Nostrand, 2016). Particularly platelets are regarded as an important source of blood amyloid peptides (Chen, Inestrosa, Ross, & Fernandez, 1995;Kucheryavykh et al, 2017). This can influence plasma Aβ levels and obscure the relationship between plasma Aβ levels and Aβ brain pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Since platelets present neuron-like metabolic pathways, previous studies have shown that in AD, APP acts as a platelet-membrane receptor contributing mostly to soluble β-amyloid after platelet activation [43]. Mitochondrial dysfunction, higher content in phosphorylated TDP43, and morphological and structural platelet changes in AD and PD have also been reported [44,45]. Whether miRNA deregulation in platelets promotes neurodegeneration or merely re ects its effects remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%